Residuality and dissipation of lufenuron applied to peas in a semi-arid zone and hazard and risk index for ingestion (Bioagro, 2023)
The frequent application of pesticides in horticultural crops can generate residues with adverse consequences on the health of consumers. The objective of this research was to determine the residual and dissipation of lufenuron applied on peas (Pisum sativum L.), and its hazard and risk index by ingestion. The study was carried out in an open field in a semi-arid zone located in Arequipa, Peru. The treatments were the application of three doses of the active ingredient lufenuron (12, 24 and 30 g·ha-1) in two opportunities (every 4 and 8 days), conforming six treatments applied via foliar in a completely randomized design, with three replications (18 plots). Lufenuron residues were detected in pea pods and grains by HPLC in samples collected 4, 8 and 16 days after the last application. Dissipation kinetics, half-life, ingestion hazard or health hazard index (HI) were calculated. The highest half-life values were 13.4 days in pods and 4.8 days in grains with the dose 24 g·ha-1 and frequency of 8 days. The application frequency was more relevant than the lufenuron dose, and the difference was detected at 4 days after the last application. It was found that lufenuron residues in grains at 4 days of sampling exceeded the maximum residue limits in all treatments; however, under the conditions of this trial, ingestion of pea grains with lufenuron residues did not represent a health hazard and risk of population.
Keywords: Pesticide; Pisum sativum; safety